Penerapan Algoritma Apostolico Dalam Pencarian Tiket Pemesanan dan Pendaftaran Seminar - Dias Syahril Nurrachman (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2021)
At the seminar, the sale of seminar tickets is done manually, that is, by registering seminar participants. Where in this activity the participants have to manually fill in the data needed to create a certificate at the end of the activity. Accordingly, internet technology can be used for online seminar registration, making it easier for seminar organizers to know the results of the accumulated seminars. In this study, a website-based seminar ticket sales system will be developed as a seminar ticket sales affiliate system, namely by helping seminar organizers to promote or market seminar ticket sales. By using this application, information becomes easier to convey and obtain, both seminar organizers and seminar participants. To provide better activity performance. The system is built using an open source PHP codeigniter framework and uses the apostolico algorithm applied to the seminar category search process on database storage by generating a list of seminar category options based on the keywords entered.